Destabilizing Orthodoxy, De-territorializing the Anthropology of Islam - Grewal, Zareena (Journal of the American Academy of Religion, 2016)
The category of “orthodoxy” remains one of the most vexed and under-theorized in religious studies. Although the common-sense usage of orthodoxy presumes it is static, fixed, and timeless, Muslims are at least as conscious of the diversity of interpretation and practice of Islam as are Western scholars of religion. Yet, Muslims are generally theologically invested in the universality and coherence of Islam. Contrary to critics who reduce the postcolonial turn in anthropology and religious studies to apologetics, I demonstrate how orthodoxy claims can be critically appraised in a discursive framework rather than constructivist or nominalist analytical modes. I write against deployments of orthodoxy framed in narrow, sectarian terms. In my analysis, orthodoxy emerges as a dynamic relation of power through the placement of contemporary Sunni intellectuals with large followings in the United States (such as Tariq Ramadan, Hamza Yusuf, and Yasir Qadhi) in a broader American Islamic intellectual history with religious leaders and thinkers such as Elijah Muhammad and Drew Ali.